A longitudinal investigation of perfectionism and repetitive negative thinking in perinatal depression - Egan, Sarah; Kane, Robert; Winton, K.; Eliot, C.; McEvoy, P. (Elsevier, 2017)
Repetitive negative thinking and perfectionism have both been proposed as processes that are related to depressive symptoms. The purpose of this study was to investigate concurrent and prospective relationships between antenatal and postnatal depression, perfectionism, and repetitive negative thinking. A longitudinal design was used and 71 women were followed from their third trimester of pregnancy to six weeks post birth. A structural equation model was tested with antenatal perfectionism predicting antenatal repetitive negative thinking, perfectionism predicting postnatal depression, and antenatal repetitive negative thinking predicting antenatal and postnatal depression. The final model provided an adequate fit to the data but the pathway from antenatal repetitive negative thinking to postnatal depression was not significant. The findings provide support for the role of perfectionism and repetitive negative thinking in the onset and maintenance of perinatal symptoms of depression. It is suggested that future research investigates the efficacy of targeting repetitive negative thinking and perfectionism in pregnancy to examine if this can reduce perinatal depression.